ANALISIS REGRESI LOGISTIK BINER PADA KARAKTERISTIK DEMOGRAFI SOSIAL EKONOMI DAN INTERVENSI GIZI SPESIFIK BALITA STUNTING DI WILAYAH KERJA PUSKESMAS JAMBULA KOTA TERNATE - Nofiandri Mochtar; Nur M Ali; Ansar Mursaha; Adhyanti (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Stunting is a chronic nutritional problem that results from prolonged malnutrition. It is also considered a malnutrition status not only due to the height of the parents but also because of various socio-economic and demographic factors. These factors include family sizes, birth spacing of children, family socio-economic status, parental education levels, parental occupations, and specific nutritional interventions, such as Early Initiation of Breastfeeding (IMD), iron and folic acid supplementation (TTD), exclusive breastfeeding, complementary feeding (MP ASI), and immunization. This research aimed to analyze the influence of socio-economic demographic characteristics and specific nutritional interventions on families with stunted toddlers in the working area of the Jambula Community Health Center. The study employed an analytical survey design, with total sampling (non-probability sampling) involving a population of stunted toddlers. The results of this research showed the following associations between socio-economic demographic characteristics and stunting: number of family members (OR = 0.842, p = 0.043 < 0.05), birth spacing (OR = 9.3, p = 0.013 < 0.05), family socioeconomic status (OR = 11.8, p = 0.045 < 0.05), father’s education (OR = 0.49, p = 0.445 > 0.05), mother’s education (OR = 1.0, p = 0.979 > 0.05), and parental occupation (OR = 0.324, p = 0.11 > 0.05). Regarding specific nutritional interventions, significant factors were Early Initiation of Breastfeeding (IMD) (OR = 0.76, p = 0.024 < 0.05), iron and folic acid supplementation (TTD) (OR = 5.9, p = 0.02 < 0.05), exclusive breastfeeding (OR = 0.6, p = 0.015 < 0.05), complementary feeding (MP ASI) (OR = 0.678, p = 0.039 < 0.05), and immunization (OR = 1.6, p = 0.016 < 0.05). In conclusion, factors that significantly influence the incidence of stunting in toddlers in the Jambula Health Center working area include the number of family members, birth spacing, family socio-economic status, Early Initiation of Breastfeeding, iron and folic acid supplementation, exclusive breastfeeding, complementary feeding, and immunization